2006
DOI: 10.1002/bio.888
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic electrochemiluminescence of acetonitrile, acetonitrile–1,10‐phenanthroline and acetonitrile–ternary Eu(III) complexes at a gold electrode

Abstract: Cathodic electrochemiluminescence (ECL) behaviours of the acetonitrile, acetonitrile-1,10-phenanthroline (phen) and acetonitrile-ternary Eu(III) complex systems at a gold electrode were studied. One very weak cathodic ECL-2 at -3.5 V was observed in 0.1 mol/L tetrabutylammonium tetrafluoroborate (TBABF(4)) acetonitrile solution. When 10 mmol/L tetrabutylammonium peroxydisulphate [(TBA)(2)S(2)O(8)] was added to 0.1 mol/L TBABF(4) acetonitrile solution, another cathodic ECL-1 at -2.7 V appeared and the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…al., reported ECL spectra of Eu(tta) 3 phen and Eu(dbm) 3 phen in the presence of S 2 O 8 2− using a Au electrode. They observed a sharp (λ ECL =∼ 610 nm) spectrum originated from the f‐f transition on top of a broad component (λ ECL =∼ 530 nm) derived from polymerized MeCN at a more negative potential than the limit of the negative end of the polarized potential window (−2.6 V vs Ag/AgCl) . Our results confirmed that the ECL based on the f‐f transitions of the Eu(III) complexes were able to be observed at a less negative potential, and coordinated ligands may cause broad emissions.…”
Section: Resultsmentioning
confidence: 99%
“…al., reported ECL spectra of Eu(tta) 3 phen and Eu(dbm) 3 phen in the presence of S 2 O 8 2− using a Au electrode. They observed a sharp (λ ECL =∼ 610 nm) spectrum originated from the f‐f transition on top of a broad component (λ ECL =∼ 530 nm) derived from polymerized MeCN at a more negative potential than the limit of the negative end of the polarized potential window (−2.6 V vs Ag/AgCl) . Our results confirmed that the ECL based on the f‐f transitions of the Eu(III) complexes were able to be observed at a less negative potential, and coordinated ligands may cause broad emissions.…”
Section: Resultsmentioning
confidence: 99%
“…[ 15 ] With addition of PVA-CN to SN, a new peak at 1103 cm −1 appears, which belongs to the stretching vibration of C-O-C on PVA-CN ( Figure S3, Supporting Information), [ 21 ] while the peak appearing at 1059 cm −1 after LITFSI and LiPF 6 dissolved in SN is assigned to the stretching vibration of S-N-S on LITFSI (Figure 3 a). [ 22 ] As shown in Figure 3 b, an obvious new peak at 1557 cm −1 assigned to the stretching vibration of C-N appears in the FTIR spectrum of PVA-CN/SN solid electrolyte, [ 23 ] indicating a new conjugated structure with C-N bonds is formed and PVA-CN monomers are successfully polymerized in the SN-based solid electrolyte.…”
Section: Characteristics Of Sensmentioning
confidence: 97%
“…25 The FTIR spectrum of the polymer matrix shows that the absorption peak at around 2250 cm À1 belonging to C^N bonds almost disappears, whereas the intensity of peak at 1670 cm À1 apparently increases, indicating the presence of C]N bonds in the polymer matrix. 26 The result of the FTIR spectrum demonstrates that the C^N bonds were cleaved in the gelation reaction of PVA-CN and a new conjugated structure with C]N bonds was formed.…”
Section: Investigation Of the In Situ Gelation Mechanismmentioning
confidence: 96%